APLIKASI RESOURCE MANAGEMENT BERBASIS WEB DAN MOBILE PADA PT ASPIRASI LUHUR - Stephanie Budianto; Lely Hiryanto; Janson Hendryli (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Every company surely need a competent and full skill emloyees to develop and follow time progress in the field of Human Resources. The problems of employees recruitment in a company is an important thing. One way to fix the problem is apply a online recruitment system with curriculum vitae that had been prepared in web application. Because employees recruitment with manual system in a company are considered hard enough. The purpose from a new employees recruitment system is to collect suitor’s data who potensial into organization. Employees recruitment system do with recommendation system based on criterias which made according companies required and expected to provide a good recommendation. To follow up an employees recruitment, in this web application is also add some features to ease Human Resource Development , that is employees data management who had worked in the company.